Fabrication of the uniform CdTe quantum dot array on GaAs substrate utilizing nanoporous alumina masks - Jung, Mi; Lee, Hong Seok; Park, Hong Lee; Lim, Han-jo; Mho, Sun-il (Current applied physics, 2006)
Fabrication of quantum dot array (QDA) is attractive for applications in electronic and optoelectronic devices. The CdTe QDAs have potential applications in optoelectronic devices of visible range. One of the major challenges in fabricating QDAs is the uniformity and reproducibility in size and spatial distribution. The uniformity and reproducibility of QDs can be improved by using the nanoporous alumina mask. The geometry of porous alumina is schematically represented as a close-packed array of columnar hexagonal cells, each containing a central pore normal to the substrate. The well-ordered nanoporous alumina masks were able to obtain by two-step anodizing processes from aluminum in oxalic acid solutions at low temperature. The pore size, thickness, and density of nanoporous alumina mask can be controlled with the anodization voltage, time, and electrolyte. The CdTe QDAs on the GaAs substrate was grown by molecular beam epitaxy method using the porous alumina masks. The temperature of substrate and source (Cd, Te) was an important factor for the growth of CdTe QDs on GaAs substrate. The CdTe QDAs of 80 nm dot size was fabricated; using the porous alumina masks (∼300 nm thickness) of pore diameter (80 nm) and density (∼10 10 /cm 2).